2019
DOI: 10.1128/mbio.00519-19
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Anthelmintic Treatment on Human Gut Microbiota Based on Cross-Sectional and Pre- and Postdeworming Comparisons in Western Kenya

Abstract: Murine studies suggest that the presence of some species of intestinal helminths is associated with changes in host microbiota composition and diversity. However, studies in humans have produced varied conclusions, and the impact appears to vary widely depending on the helminth species present. To demonstrate how molecular approaches to the human gut microbiome can provide insights into the complex interplay among disparate organisms, DNA was extracted from cryopreserved stools collected from residents of 5 ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 54 publications
(94 reference statements)
3
55
1
Order By: Relevance
“…While albendazole treatment may have had some effect on the microbiome, we believe that this is likely limited. Recent studies in Indonesia and Kenya found statistically significant but small changes in the microbiome that could have been a direct result of albendazole treatment [56, 57]. Since prevalence in our study site was so high (96%) that we did not have an uninfected post-deworming control group, we believe the strongest evidence of changes resulting from worm clearance are those where changes are correlated with the decrease in egg burden ( Fig 4 ) and those in which the post-deworming phenotype reverts to a more urban-like phenotype ( Fig 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…While albendazole treatment may have had some effect on the microbiome, we believe that this is likely limited. Recent studies in Indonesia and Kenya found statistically significant but small changes in the microbiome that could have been a direct result of albendazole treatment [56, 57]. Since prevalence in our study site was so high (96%) that we did not have an uninfected post-deworming control group, we believe the strongest evidence of changes resulting from worm clearance are those where changes are correlated with the decrease in egg burden ( Fig 4 ) and those in which the post-deworming phenotype reverts to a more urban-like phenotype ( Fig 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/nrmicro microbiota, leading to increases in SCFA production and pulmonary T reg cells 118 . Associative studies suggest that helminth infection encourages gut bacterial diversity that is protective against asthma in humans [118][119][120] . The hygiene hypothesis in atopic diseases may thus relate to both protective colonization and infections that mediate immune-microorganism interactions in local and distant tissues.…”
Section: Vitiligomentioning
confidence: 99%
“…Gastrointestinal parasites may modulate intestinal inflammation, malabsorption, and microbiome changes [22][23][24][25][26]. The microbiome is associated with digestion, nutrition and health, but alterations in biodiversity can increase disease states and induce intestinal inflammation [27].…”
mentioning
confidence: 99%